Fostering Engagement and Creativity through Programming: The Beauty and Joy of Computing in a First-year Engineering class - Meza, Federico; Torres, Nicolas; Vasquez, Andrea (2020 39th International Conference of the Chilean Computer Science Society (SCCC), 2020)
There is a growing interest in learning computer programming even among students from majors other than computer science (CS). Many universities offer a common Introduction to Programming (CS1) course, but this approach is usually detrimental to those who are not pursuing a CS major. This article is an experience report that summarizes the results of adapting and implementing the course "The Beauty and Joy of Computing" (BJC) in an Engineering in Product Design first-year class, a group that showed below-average performance in the past. BJC is a course for undergraduate non-CS majors at UC Berkeley, designed to broaden student participation in Computer Science. After a fully online semester of BJC at UTFSM, students showed greater responsibility and commitment when compared to previous cohorts. They also reported greater satisfaction with programming while having a lower attrition rate and comparable final grades to students in the regular CS1 class.